ANTIBACTERIAL ACTIVITY OF TABERNAEMONTANA STAPFIANA BRITTEN (APOCYNACEAE) EXTRACTS - Okemo, Paul Owuor; Ruttoh, Ernest Kiprono; Tarus, Paul Kipkosgei; Bii, Christine Chemutai; Machocho, Alex King’ori; Karimi, Lucas Kaime (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
Antibacterial and phytochemical screening of methanolic, sequential extracts (hexane, dichloromethane, ethyl acetate and methanol) and alkaloid rich fractions of Tabernaemontana stapfiana Britten was carried out. The phytochemical screening showed the presence of alkaloids, flavonoids, coumarins, tannins and saponins that have been associated with antimicrobial activity. The stem and root bark methanolic extracts showed good activity against the bacterial strains used including the multiple drug resistant Staphylococcus aureus strain with minimum inhibitory concentrations ranging from 15.6 to 500 g/ml and minimum bactericidal concentrations ranging from 31.25 to 500 g/ml. The sequential extracts of the root and stem bark had high antimicrobial activity with minimum inhibitory concentrations (MICs) ranging between 3.9 and 250 g/ml and minimum bactericidal concentrations (MBCs) ranging between 7.8 and 500 g/ml against the tested microorganisms. The dichloromethane extract of the alkaloid rich fractions however exhibited reduced antibacterial activities as compared to methanol and sequential extracts but the dichloromethane:methanol (4:1) mixture showed high activity with MICs ranging between 15.6 and 250 g/ml. These antibacterial efficacy studies suggest that Tabernaemontana stapfiana Britten could be a source of antibacterial agents.